Pengembangan Produk Souvenir Sabun Padat Menggunakan Minyak Goreng Sawit pada Ibu PKK Kelurahan Rawamangun Jakarta Timur - Suherman, Suherman; Haro, Andrian; Dalimunthe, Sholatia (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2018)
Nowadays, solid and transparent soap is often used as a display of wedding souvenirs, air freshener, and handicrafts. With the presence of a solid and transparent soap in very unique display and interesting this can make the soap is sold at a relatively more expensive price in the market. Regarding with the development of solid soap products that can produce several good benefits, this activity needs to be trained, developed and empowered to the parties who have the potential to produce these products. One of the parties that has the potential to be trained is the housewives in the PKK group (Family Welfare Empowerment) at Rawamangun, East Jakarta. This community service activity is done by using lecture and simulation/demonstration method through innovative product development of souvenir soap by using palm cooking oil. The results of the training show the enthusiasm and willingness of the participants to be able to perform individually in the manufacture of solid soap souvenir products and they can produce in large quantities. With this training, the housewives can practice themselves at home and be motivated to open business opportunities through these product so it can be feasible for sale in the market